2006
DOI: 10.2355/isijinternational.46.180
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Phosphorous Transfer from CaO-FetO-P2O5(-SiO2) Slag to CaO Particles

Abstract: Lime particles (0.5 to 1 mm) were added by dropping to CaO-Fe t O-P 2 O 5 slag at 1 400°C, followed by stirring and the reaction products near a CaO particle/slag interface were determined by a microprobe analysis (EPMA-EDX). The 3CaO · P 2 O 5 and 4CaO · P 2 O 5 phases were crystallized depending on the amount of added CaO particles which are rapidly dissolved after the contact with a molten slag. The phosphorous distribution ratios between calcium phosphates and CaO-Fe t O slag obtained at temperatures betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 9 publications
2
59
0
1
Order By: Relevance
“…Since many studies 1,[4][5][6][7][8][9] had confirmed that phosphorus in the liquid phase can be fixed into the 2CaO · SiO 2 -3CaO · P 2 O 5 solid solution or compounds by CaO contained in the steelmaking slag, the idea is proposed to innovate the present refining process by promoting the transfer of phosphorus from liquid phase to solid phase for better dephosphorization. Reduction of the lime consumption and slag emission can be achieved by improving the utilization efficiency of solid CaO or 2CaO · SiO 2 phase in the steelmaking slag.…”
Section: Introductionmentioning
confidence: 99%
“…Since many studies 1,[4][5][6][7][8][9] had confirmed that phosphorus in the liquid phase can be fixed into the 2CaO · SiO 2 -3CaO · P 2 O 5 solid solution or compounds by CaO contained in the steelmaking slag, the idea is proposed to innovate the present refining process by promoting the transfer of phosphorus from liquid phase to solid phase for better dephosphorization. Reduction of the lime consumption and slag emission can be achieved by improving the utilization efficiency of solid CaO or 2CaO · SiO 2 phase in the steelmaking slag.…”
Section: Introductionmentioning
confidence: 99%
“…Urban, 2015) [2] Na maioria dos casos, escórias utilizadas em desfosforação são básicas e, portanto, saturadas em silicato dicálcico, 2CaO.SiO₂ (também chamado de C₂S). Sabe-se que o silicato dicálcico e o fosfato tricálcico formam uma solução sólida ao longo de uma ampla gama de composição, o 2CaO.SiO₂-3CaO.P₂O₅ (C₂SC₃P) [3]. Em seu trabalho, Campos demonstrou matematicamente que as reações de desfosforação ocorrem somente na interface entre o metal e a escória [4].…”
Section: Introductionunclassified
“…2,3) However, blast furnace slag and steel slag used as agricultural fertilizer and soil improvement is totally 230 000 tons in China 2010, accounts for 0.5% of total blast furnace slag and steel slag using amount, so the utilization of steel slag for fertilizer is very low.…”
Section: Effect Of Na 2 O On Phosphorus Enrichment and Separation In mentioning
confidence: 99%
“…Lu LIN, 1,2) * Yan-ping BAO, 1) Wei JIANG 3) and Qi-fan WU 3) Journals Publishing Center, University of Science and Technology Beijing, 30 Xueyuan Rd., Haidian, Beijing, 100083 China.…”
Section: Effect Of Na 2 O On Phosphorus Enrichment and Separation In mentioning
confidence: 99%